SOCIAL DEVELOPMENT OF FOOD SECURITY IN MARINGKIK ISLAND VILLAGE, EAST LOMBOK REGENCY, WEST NUSA TENGGARA PROVINCE - Rahman, Abdul; Utama, Lalu Satria; Rozie, Azharisman; Supratman, Supratman (CosmoGov: Jurnal Ilmu Pemerintahan, 2026)
This study aims to analyze economic development strategies in increasing food security in Maringkik Island Village, Keruak District, East Lombok Regency. This small village faces various challenges, including limited natural resources, the threat of coastal erosion, climate change, and limited access to basic services. The results of the study show that the people of Maringkik Island have high social resilience in facing limitations and disaster threats. They implement a family-based division of labor system as an adaptation strategy. However, efforts to improve food security still require a more structured approach, especially in developing basic infrastructure, managing the environment, and strengthening community capacity. The recommendations of this study include improving basic infrastructure such as clean water and renewable energy, providing capital schemes for local MSMEs, strengthening disaster mitigation programs, and synergy between the government, the community, and the private sector. A disaster mitigation model that involves stakeholders makes a tangible contribution to increasing participation in the formulation of economic development policies aimed at enhancing sustainable food security.